Mechanism and behavior of fiber-reinforced asphalt mastic at high temperature. Issue Volume 19:Issued 5(2018) (4th May 2018) - Zhang, Xiaoyuan; Gu, Xingyu; Lv, Junxiu; Zhu, Zongkai; Ni, Fujian
Abstract: The rheological behaviour and reinforcement mechanism of asphalt mastic mixed with fibres at high temperature were investigated in this study. Fibres, including basalt, polyester and glass, were added to asphalt mastic. Repeated creep and multi-stress creep tests were conducted to characterise the high-temperature properties of the mastic, and numerical simulation was performed with ABAQUS software to analyse the reinforcement effect of fibres. Test results indicate that the fibres have excellent reinforced performance; for example, the accumulated strain and its change rate decrease, and its creep stiffness modulus increases after the fibres are mixed into the mastic. The creep recovery rate increases, and its creep residual value decreases at a high stress level. The creep stiffness modulus under different loading cycles can be expressed by a power function. Numerical simulation shows that the fibres effectively absorb mastic stress; hence, creep strain in the mastics decreases. The Burgers model was utilised to present the rheological behaviours of mastics with fibres; the model parameters were estimated.